Белый голубь - Жариков Андрей Дмитриевич (Просвещение, 1990)
Экземпляры: ф.14 (1990) / Инвентарный номер: 31496 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ж 34 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-44